Effects of mechanical grinding on the physicochemical properties of silica aerogels - Li, Rutian; Zeng, Shuisheng; Shen, Kai; Wang, Guichao; Zhang, Jun (Frontiers in Materials, 2023)
Mechanical grinding is a facile method to get silica aerogels (SAs) with various particle sizes.In this study, we concentrated on the effects of grinding time and grinding speed on the physical and chemical properties of SAs. The results reveal that the physicochemical properties of SAs are more sensitive to the grinding speed rather than the grinding time. When the grinding speed is over 200 rpm, large particles of SAs are crushed into smaller particles with obviously decreasing particle sizes and the silica skeletons of SAs have collapsed. The reduction of particle sizes and the collapse of skeleton lead to an increase in both the tap density and thermal conductivity.Therein, the thermal conductivity is positively proportional to the density. Furthermore, the grinded SA powders still possess the contact angles over 135°, indicating the good hydrophobicity.All these demonstrate that the mechanical grinding has evident effects on the microstructure, density, thermal conductivity and particle sizes, which further impact the performance of SAs during the practical applications. Thus, the mechanical grinding can be employed to obtain the SAs with different particle sizes, however, the appropriate grinding parameters must be determined to ensure that the structure and performance of SAs are acceptable.